Prenatal Exposure to Polycyclic Aromatic Hydrocarbons /Aromatics, BDNF and Child Development - Perera, Frederica (Environ Res, 2015)
OBJECTIVES: Within a New York City (NYC) birth cohort, we assessed the associations between polycyclic aromatic hydrocarbon (PAH) and other aromatic DNA adducts and brain derived neurotrophic factor (BDNF) concentrations in umbilical cord blood, and neurodevelopment at age 2 years and whether BDNF is a mediator of the associations between PAH/aromatic-DNA adducts and neurodevelopment. METHODS: PAH/aromatic-DNA adduct concentrations in cord blood were measured in 505 children born to nonsmoking African-American and Dominican women residing in NYC, and a subset was assessed for neurodevelopment at 2 years using the Bayley Scales of Infant Development Mental Development Index (MDI). A spectrum of PAH/aromatic-DNA adducts was measured using the (32)P-postlabeling assay; DNA adducts formed by benzo[a]pyrene (B[a]P), a representative PAH, were measured by High Performance Liquid Chromatography (HPLC)/fluorescence. BDNF mature protein in cord blood plasma was quantified by an ELISA. Multivariate regression analysis, adjusting for potential confounders, was conducted. RESULTS: PAH/aromatic-DNA adduct concentration measured by postlabeling was inversely associated with BDNF concentration (p=0.02) and with MDI scores at 2 years (p=0.04). BDNF level was positively associated with MDI scores (p=0.003). Restricting to subjects having all three measures (PAH/aromatic-DNA adducts by postlabeling, MDI, and BDNF), results were similar but attenuated (p=0.13, p=0.05, p=0.01, respectively). Associations between B[a]P-DNA adducts and BDNF and B[a]P-DNA adducts and MDI at age 2 years were not significant. At age 3 years, the positive association of BDNF with MDI was not observed. CONCLUSIONS: The results at age 2 suggest that prenatal exposure to a spectrum of PAH/aromatic pollutants may adversely affect early neurodevelopment, in part by reducing BDNF levels during the fetal period. However, the same relationship was not seen at age 3.